5. HEALTH-RELATED QUALITY OF LIFE OF PATIENTS WHO UNDERWENT POSTPARTUM ABDOMINOPLASTY (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the health-related quality of life (HRQoL) of patients after postpartum abdominoplasty.Method: A prospective study was conducted on 66 patients at Hanoi Medical University Hospital from January 2022 to December 2024. Assessments were made using the BODY-Q scale and the 15D instrument.Results: The average patient age was 38.8 years. Among them, 71.2% underwent surgery due to functional issues related to excess skin, and 48.5% after weight loss through diet and exercise. In the 15D scale, the highest scores were observed in eating (0.98 ± 0.05), speech (0.96 ± 0.07), and vision (0.95 ± 0.08), while the lowest were in discomfort and symptoms (0.70 ± 0.20), sexual activity (0.75 ± 0.18), and hearing (0.75 ± 0.18). On the BODY-Q scale, physical function had the highest score (80 ± 15), followed by scars (75 ± 20), body image (60 ± 18). The strongest correlations with HRQoL were found in body image (0.65, p < 0.001), physical function (0.64, p < 0.001), and psychological well-being (0.66, p < 0.001).Conclusion: Postpartum abdominoplasty significantly improved body image, physical function, and psychological well-being. However, a more comprehensive approach is needed, not only focusing on aesthetic enhancement but also addressing psychological factors to improve the overall quality of life for postpartum women.
Keywords: Abdominoplasty; postpartum; BODY-Q, 15D